Therapeutic effects of serum extracellular vesicles in liver fibrosis - Chen, Li; Chen, Ruju; Kemper, Sherri; Cong, Min; You, Hong; Brigstock, David R. (Journal of extracellular vesicles, 2018)
The lack of approved therapies for hepatic fibrosis seriously limits medical management of patients with chronic liver disease. Since extracellular vesicles (EVs) function as conduits for intercellular molecular transfer, we investigated if EVs from healthy individuals have anti-fibrotic properties. Hepatic fibrogenesis or fibrosis in carbon tetrachloride (CCl 4 )- or thioacetic acid-induced liver injury models in male or female mice were suppressed by serum EVs from normal mice (EVN) but not from fibrotic mice (EVF). CCl 4 -treated mice undergoing EVN therapy also exhibited reduced levels of hepatocyte death, inflammatory infiltration, circulating AST/ALT levels and hepatic or circulating pro-inflammatory cytokines. Hepatic histology, liver function tests or circulating proinflammatory cytokine levels were unaltered in control mice receiving EVN. As determined using PKH26-labelled EVN, principal target cells included hepatic stellate cells (HSC; a normally quiescent fibroblastic cell that undergoes injury-induced activation and produces fibrosis during chronic injury) or hepatocytes which showed increased EVN binding after, respectively, activation or exposure to CCl 4 . In vitro, EVN decreased proliferation and fibrosis-associated molecule expression in activated HSC, while reversing the inhibitory effects of CCl 4 or ethanol on hepatocyte proliferation. In mice, microRNA-34c, -151-3p, -483-5p, -532-5p and -687 were more highly expressed in EVN than EVF and mimics of these microRNAs (miRs) individually suppressed fibrogenic gene expression in activated HSC. A role for these miRs in contributing to EVN actions was shown by the ability of their corresponding antagomirs to individually and/or collectively block the therapeutic effects of EVN on activated HSC or injured hepatocytes. Similarly, the activated phenotype of human LX-2 HSC was attenuated by serum EVs from healthy human subjects and contained higher miR-34c, -151-3p, -483-5p or -532-5p than EVs from hepatic fibrosis patients. In conclusion, serum EVs from normal healthy individuals are inherently anti-fibrogenic and anti-fibrotic, and contain microRNAs that have therapeutic actions in activated HSC or injured hepatocytes. Abbreviations: ALT: alanine aminotransferase; AST: aspartate aminotransferase; CCl 4 : carbon tetrachloride; CCN2: connective tissue growth factor; E: eosin; EGFP: enhanced green fluorescent protein; EVs: extracellular vesicles; EVF: serum EVs from mice with experimental hepatic fibrosis; EVN: serum EVs from normal mice; H: hematoxylin; HSC: hepatic stellate cell; IHC: immunohistochemistry; IL: interleukin; MCP-1: monocyte chemotactic protein-1; miR: microRNA; mRNA: messenger RNA; NTA: nanoparticle tracking analysis; PCNA: proliferating cell nuclear antigen; qRT-PCR: quantitative real-time polymerase chain reaction; SDS-PAGE: sodium dodecyl sulphate - polyacrylamide gel electrophoresis; αSMA: alpha smooth muscle actin; TAA: thioacetic acid; TG: transgenic; TGF-β: transforming growth factor beta; TEM: transmission electron microscopy; TNFα: tumour necrosis factor alpha.